Optimizing Health Educated Family to Reduce Hypertension and Integrated Diabetes Mellitus in Bligo - Rasyidah, Hanna; Purnomo, Halim; Amieni, Nada Nadiva Aisy; Ufaira, Naura; Ramadhan, Naufal Raihan; Nisa, Lia Fakila; Nisa, Zalfaa Hanifatun; Salam, Amri Adi Nur; Narpati, Dipo Andang; Anindhita, Dyah Raras; Al-Ghazali, Ersan; Qosthori, Hiban; Hani’ah, Marsya Nadiyyatul; Mahfudz, Muhammad Imam; Agwa, Mullah Muhammad; Nurfiana, Nurfiana; Afaki, Sajida Fihrisa; Riyani, Sri; Wahyuningsih, Tri (Bangun Desa: Jurnal Pengabdian Masyarakat, 2024)
The Community Service Program (KKN) conducted in Bligo Village, Buaran District, Pekalongan Regency, aimed to optimize the Family Guidance program in reducing hypertension and diabetes mellitus rates. The program included various activities such as health education, screening, and family guidance for high-risk individuals. The results showed a decrease in blood pressure and blood sugar levels among participants, accompanied by lifestyle changes towards healthier habits. The success of this program highlights the importance of active community participation and support from various stakeholders in addressing non-communicable health issues within the community